Praktik Hidup Sehat Pemukim di Kawasan Percandian Muarajambi Pada Abad ke-7 Hingga 11 M.: Praktik Hidup Sehat Pemukim Percandian Muarajambi pada Abad Ke-7 Hingga Abad ke-11 M - Sadzali, Asyhadi Mufsi; Agus Aris Munandar; Retno Purwanti; ali akbar; Wahyu Rizky Andhifani (Berkala Arkeologi, 2025)
Archaeological research in the Muarajambi temple area has indicated its past function as a place for learning Buddhist teachings, inhabited by settlers between the 7th and 12th centuries AD. Its location near the Batanghari River and tropical forests made the settlers vulnerable to health disturbances. Starting with this phenomenon, the question arises: what was the picture of healthy living practices of the settlers in the Muarajambi Temple Complex between the 7th and 12th centuries AD? This research uses K. Dark's archaeological method with Ian Hodder's entanglement theory analysis to examine the relationship between excavation data from Candi Koto Mahligai and Kedaton, I-Tsing's records, and the surrounding environment. There is a possibility that 1) the implementation of the Mahavihara Muarajambi settlers' regulations not only trained spirituality but also physical and mental health; 2) from the pollen data of medicinal plants, it is possible that the students developed medical knowledge; 3) pollen data and the analysis of the functions of medicinal plants provide an overview of the types of diseases suffered by the settlers; and 4) the discovery of artifacts and features at the Muarajambi Temple strengthens the similarity of hypotesa with the narrative of healthy living practices in the I-Tsing text.